INTEGRATION OF SAFETY ANALYSIS USING HAZOPS AND FTA ON PRECIPITATION PROCESS IN URANIUM REFINING AND CONVERSION FACILITY - Oktavianto, Putra; Saputra, Ade; Sholikhah, Mu’nisatun (Urania: Jurnal Ilmiah Daur Bahan Bakar Nuklir, 2025)
Implementation of safety at nuclear facilities must be implemented as well as possible. This is related to safety, especially for operators who carry out the process directly. In the uranium refining and conversion facility, safety analysis using HIRADC has been implemented to support safety in carrying out the process, especially in the uranyl nitrate precipitation process. However, this is not enough to ensure that safety during the precipitation process at the uranium refining and conversion facility can be maintained. To complement the existing HIRADC, another safety analysis is needed. Therefore, HAZOPS and FTA were analysed. This HAZOPS analysis will complement the safety side of the facility using an indicator control system that will automatically eliminate the risk of hazards that occur during the operation of the facility, while the FTA will analyse the causes of failure that can cause accidents so that the causal factors of the accident can be identified. From the results of the HAZOPS analysis, it was found that there was 1 potential hazard that fell into the low risk category, and 11 potential hazards that fell into the medium risk category. While the results of the FTA analysis obtained 15 events that cause product failure in the precipitation tank. From the results of the safety analysis that has been carried out, it can be concluded that HAZOPS and FTA can complement HIRADC to ensure safety can be maintained during the process.